2017
DOI: 10.1371/journal.pone.0175656
|View full text |Cite|
|
Sign up to set email alerts
|

Functional analysis of the GmESR1 gene associated with soybean regeneration

Abstract: Plant regeneration can occur via in vitro tissue culture through somatic embryogenesis or de novo shoot organogenesis. Transformation of soybean (Glycine max) is difficult, hence optimization of the transformation system for soybean regeneration is required. This study investigated ENHANCER OF SHOOT REGENERATION 1 (GmESR1), a soybean transcription factor that targets regeneration-associated genes. Sequence analysis showed that GmESR1 contained a conserved 57 amino acid APETALA 2 (AP2)/ETHYLENE RESPONSE FACTOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Zhang et al cloned the gene GmESR1, related to soybean regeneration. The functional analysis confirmed that this gene promoted soybean regeneration [9]. Zhou et al cloned the soybean regeneration-related gene GmWUS, indicating that it participates in the differentiation and regeneration of cluster buds and improves the regeneration ability of soybean [10].…”
Section: Introductionmentioning
confidence: 96%
“…Zhang et al cloned the gene GmESR1, related to soybean regeneration. The functional analysis confirmed that this gene promoted soybean regeneration [9]. Zhou et al cloned the soybean regeneration-related gene GmWUS, indicating that it participates in the differentiation and regeneration of cluster buds and improves the regeneration ability of soybean [10].…”
Section: Introductionmentioning
confidence: 96%